Accountability and opposition to globalization in international assemblies - Pieter de Wilde; Wiebke Marie Junk; Tabea Palmtag (European journal of international relations, 2016)
Advocates of a global democratic parliament have expressed hopes that this would not only legitimize global governance in procedural terms, but also bring about more cosmopolitan policies. They point to the European Parliament as an example of a successful real existing democratic parliament beyond the state with cosmopolitan intent. We analyse plenary debates in the United Nations General Assembly and the European Parliament about the issues of climate change, human rights, migration, trade and European integration between 2004 and 2011 to study the nature of opposition to cosmopolitanism within these two assemblies. We find more vocal and better-organized opposition to cosmopolitanism in the European Parliament than in the United Nations General Assembly. We demonstrate the plausibility that direct and more proportional mechanisms of delegation and accountability in the case of the European Parliament account for this observed difference. Should further research confirm these initial findings, advocates of a global democratic parliament may find that an empowered democratic World Parliament would support less cosmopolitan policies than the current United Nations General Assembly.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich. / This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively.
Keywords: 330; Claims analysis; cleavage; cosmopolitanism; European Parliament; globalization; United Nations General Assembly